Parliamentary options for a multi-ethnic state: sovereignty, frontier governance, and representation in early twentieth-century China - Bender De Moniz Bandeira, Egas Bernard (Parliaments, Estates and Representation, 2022)
This article reconstructs two modes of parliamentary representation of (post-)imperial diversity in early twentieth-century China. One model foresaw a differentiated representation of the borderlands in the nascent parliamentary institutions, using upper house seats to garner loyalty from the nobility at the same time as it denied electoral participation. The second model stipulated electoral equality between the borderland regions and the inner provinces. While the first model parliamentarized imperial forms of governance, it was also informed by and partially conformed to global models of governance. The second was informed by notions of undivided national sovereignty. In the late Qing Empire, the government decided against the second model, for it was deemed to presuppose a degree of national integration not given in the Empire. The challenges posed by the proclamation of the Republic of China, in particular the declarations of independence of Mongolia and Tibet, led to a strong emphasis on the newly-founded state’s unity and the swift adoption of the second model. This choice, however, was neither uncontested nor was its implementation complete.
CRIS-Team Scopus Importer:2022-04-22
Keywords: borderlands; Canyiyuan (Senate); Mongolia; parliamentarism; Qing Empire; Republic of China